2021
DOI: 10.1016/j.omtm.2021.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Cas9 protein delivery non-integrating lentiviral vectors for gene correction in sickle cell disease

Abstract: Gene editing with the CRISPR-Cas9 system could revolutionize hematopoietic stem cell (HSC)-targeted gene therapy for hereditary diseases, including sickle cell disease (SCD). Conventional delivery of editing tools by electroporation limits HSC fitness due to its toxicity; therefore, efficient and non-toxic delivery remains crucial. Integrating lentiviral vectors are established for therapeutic gene delivery to engraftable HSCs in gene therapy trials; however, their sustained expression and size limitation prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The SCD mutation-targeting guide RNA allowed more specific editing for the bs-globin sequence, but less for the normal b-globin sequence, evaluated by a lentiviral delivery system. 16 For these early development studies, we used b-globin donor DNA that also included synonymous base pair changes that introduced a new HindIII enzyme site (6 bases). We detected $30% HDR-mediated HindIII site insertion in the bs-globin gene as evaluated by both enzyme digestion of polymerase chain reaction (PCR) products (Figure S1C) and targeted deep sequencing (Figure S1D).…”
Section: Therapeutic-level Gene Correction Of the Scd Mutation In Patient Cd34 + Cells With Electroporation Of Editing Toolsmentioning
confidence: 99%
“…The SCD mutation-targeting guide RNA allowed more specific editing for the bs-globin sequence, but less for the normal b-globin sequence, evaluated by a lentiviral delivery system. 16 For these early development studies, we used b-globin donor DNA that also included synonymous base pair changes that introduced a new HindIII enzyme site (6 bases). We detected $30% HDR-mediated HindIII site insertion in the bs-globin gene as evaluated by both enzyme digestion of polymerase chain reaction (PCR) products (Figure S1C) and targeted deep sequencing (Figure S1D).…”
Section: Therapeutic-level Gene Correction Of the Scd Mutation In Patient Cd34 + Cells With Electroporation Of Editing Toolsmentioning
confidence: 99%
“…Recently, another study demonstrated that the NILV approach can overcome immune rejection and allow for the growth of transduced cells in an immunocompetent host by producing CRISPR-modified murine cell lines using mutated integrase vectors [ 137 ]. In addition to the advantages of the CRISPR/Cas9 system, another study proved that a Cas9 protein delivery system with NILVs encoding both guide RNA and donor DNA resulted in efficient DNA breakage, one-time genome correction of the sickle cell disease (SCD) mutation, and long-term engraftment of HSCs [ 126 ]. These studies explained the use of combined NILV approaches for a safer, long-lasting, and fruitful outcome in future research.…”
Section: Clinical Application Of Nilvsmentioning
confidence: 99%
“…IDLVs have been developed to prevent lentiviral integration into the targeted cell genome with efficient transduction [ 190 ]. IDLVs can deliver ZFN as well as CRISPR/Cas9 cargo to a broad range of dividing and quiescent tissues [ 191 , 192 ]. However, only a few studies of in vivo gene editing using LV delivery of CRISPR/Cas9 cargos have been reported in model animals.…”
Section: In Vivo Gene Editing For Scdmentioning
confidence: 99%